Ocular manifestations for misdiagnosing acute angle closure secondary to lens subluxation - Wang, Xinyu; Wang, Qian; Song, Wenqi; Yang, Yu; Zhang, Ruixuan; Lifen, Gao; Lu, Hui (Frontiers in Medicine, 2024)
Introduction The objective of this study was to assess the clinical characteristics and biometric parameters, as measured by the IOLMaster, of patients suffering from acute secondary angle closure due to zonular dialysis (ASAC-ZD) who were misdiagnosed with acute primary angle closure (APAC). Methods In this retrospective study, 34 ASAC-ZD and 39 APAC eyes were examined. Sex, age, best-corrected visual acuity, axial length (AL), anterior chamber depth (ACD), anterior chamber depth standard deviation (ACDSD), lens thickness (LT), and lens thickness standard deviation (LTSD) were measured using the IOLMaster and compared between the two groups. In addition, the difference in ACD (ACD difference) between the affected eye and the contralateral eye was analyzed. Logistic regression analysis was performed to determine the predictive factors of lens subluxation. To determine the appropriate cutoff values for biometric parameters, ROC curves were constructed to distinguish between ASAC-ZD, APAC, and cataracts. Results Compared to the APAC group, the ASAC-ZD group was younger (69.92 ± 9.345, 63.74 ± 6.947), had longer AL (22.39 ± 0.7852, 23.23 ± 1.168), shallower ACD (2.120 ± 0.2986, 1.889 ± 0.5167), higher ACDSD (7.605 ± 5.425, 9.941 ± 6.120), higher LTSD (28.00 ± 19.52, 39.79 ± 22.74), and larger ACD differences (−0.1249 ± 0.2349, −0.7306 ± 0.5332) in the affected eye. Younger age, longer AL, lower ACD, higher LTSD, and higher ACD differences were associated with lens subluxation in the univariate logistic regression analysis. ACD difference (p = 0.0003), age (p = 0.0024), and ACD (p = 0.0491) were significantly associated with lens subluxation in the multivariable logistic regression analysis. Furthermore, the ROC curve analysis showed that the cutoff values for lens subluxation were a difference in ACD of 0.225 mm and 1.930 mm. Conclusion Asymmetric ACD in both eyes with normal AL and increasing ACDSD and LTSD may support the clinical diagnosis of lens subluxation.